Assessment Leadership Model for Malaysia: A Conceptual Approach - Appanna, Sheela Kumari; A. Ghani, Muhammad Faizal; Radzi, Norfariza Mohd (Proceedings Series of Educational Studies, 2024)
The need for an effective leadership in assessment has become increasingly significant in the Malaysian educational context. This concept paper discusses the changing dynamics of educational assessment, emphasising the significance of classroom assessment in promoting student learning. The discussion initiates by delineating the diverse categories of educational assessments and emphasise the increasing significance of classroom assessment in fostering effective learning environments. In Malaysia, there is a noticeable shift from a traditional exam-oriented culture to a more holistic, learning-centred approach. However, this shift presents various obstacles, especially for teachers in successfully executing classroom assessment. Thus, this paper highlights the pivotal role of school leaders in facilitating and assisting teachers as they navigate these challenges. It emphasises on the need for establishing a strong assessment leadership model that acts as a framework for school leaders, enabling them to offer essential direction and support to their teachers. Although current frameworks and standards provide valuable insights, they frequently do not meet the contextual and contemporary requirements of the Malaysian education system. Therefore, this paper provides a foundation for future research and advocates for the development of a contextualized and contemporary assessment leadership model that aligns with both the current educational landscape and the nation's cultural context. A model that is anticipated to enhance the ability of school leaders to effectively support teachers in fostering a culture of continuous learning.